Biological tapering and sonographic flare in rheumatoid arthritis - Ko, Chi-Hua (J Investig Med, 2018)
This study aimed to evaluate the risk of ultrasound-detected synovitis after antitumor necrosis factor (TNF) tapering in patients with rheumatoid arthritis. We recruited patients with rheumatoid arthritis who accepted TNF tapering. Gray-scale synovitis and power Doppler score in bilateral wrists at the dorsal radiolunate joint were evaluated. We defined a sum of bilateral wrist scores of ≥2 as sonographic inflammation. Logistical regression analysis was used to adjust for confounding factors. One hundred and twenty-two patients who received a tapered dose of anti-TNF were enrolled, of whom 96 (78%) had ultrasound-detected synovitis and 26 had no inflammation. There were no significant differences in age, gender, body mass index, antinuclear antibodies, rheumatoid factor or anticitrullinated protein antibodies between the inflammation and non-inflammation groups. Moderate tapering of anti-TNF (tapering 50%) was more common in the patients with ultrasound-detected synovitis than mild tapering (tapering 25%) (68.8% vs 38.5%, p=0.005). After adjusting for age, body mass index, gender and a 28-joint Disease Activity Score, the moderate tapering group still had a higher risk of ultrasound-detected synovitis (OR 5.786, 95% CI 1.986 to 16.852; p=0.001); that is, the moderate tapering group had a 5.786 times higher risk of developing sonographic inflammation than the mild tapering group. The dose of biological tapering was the major determinant of ultrasound synovitis. Patients with moderate tapering had a higher risk of synovitis than those with mild tapering. We recommend not tapering by more than 25% to reduce subclinical inflammation and future joint damage.